Web-based lecture system using slide sharing for classroom questions and answers. (19th July 2010) - Iribe, Yurie; Nagaoka, Hiroaki; Kouichi, Katsurada; Nitta, Tsuneo
One of today's hottest topics in the field of education is the effectiveness of Learning Management Systems have introduced text chat, bulletin boards into the classroom. However, these systems do not provide visual explanation, by drawing diagrams or numbers on the presentation slides. We developed a classroom lecture system that encourages teacher-to-student and student-to-student communication by means of sharing slides drawn notes using a digital pen. The teacher and students can confirm the explanation by sharing these slides. As a result, enhanced understanding is achieved through classroom questions and answers using both text and visual explanation.